A new theropod (Dinosauria) from the Huincul Formation (Late Cretaceous) of north Patagonia, Argentina - Coria, Rodolfo (2010)
The theropod diversity of the Huincul Formation (Neuquén Group) includes the abelisaurids Ilokelesia and Skorpiovenator, and the carcharodontosaurid Mapusaurus. Here we report the remains of a recently collected theropod specimen (MOZ-PV-7200) from sediments assigned to this unit, which consists in 14 vertebral elements (including fragments of cervical, 2 complete dorsals, several isolated dorsal centra, one complete anterior caudal, one anteriormid caudal haemal arch, and several isolated caudal centra), a sacrum formed by 5 fused vertebrae and two isolated sacral centra, a complete right ilium and both pubes lacking the distal foot. The remains represent a mediun size, sub-adult specimen that exhibit some features that have not been described in any other previously recorded theropod form, such as a long preacetabular process of the ilium strongly projected ventrally beyond the distal end of the pubic peduncle. The presence of sacral neural spines completely fused to each other in a single longitudinal bone-sheet has been observed in the noasaurid Masiakasaurus. An ilium with a squared outlined postacetabular process with a concave distal border is a character present in most abelisaurids like Carnotaurus, Aucasaurus and Majungasaurus. Some morphological elements of the pubis remind the putative noasaurid Bahariasaurus, although further comparisons are difficult due the lost of the type specimen of this African form. By other hand, the absence of lateral pleurocoels in dorsal vertebrae reminds the condition observed in Ilokelesia aguadagrandensis Coria and Salgado. However, the sacrum formed by 5 fused elements with its centra dorsoventrally depressed and laterally wide, pubis with anteroposteriorly narrow shafts and opened obturator notch, and the absence of fusion between ilium and pubis are plesiomorphic stages for abelisaurids. The cladistic analysis currently conducted will shed light on the phylogenetical and taxonomical implications of this new specimen on the theropod diversity of the Huincul Formation.